Incidence rates, emerging serotypes and genotypes, and antimicrobial susceptibility of pneumococcal disease in Taiwan: A multi-center clinical microbiological study after PCV13 implementation. Issue 6 (June 2022) - Chen, Chih-Ho; Janapatla, Rajendra Prasad; Su, Lin-Hui; Li, Hsin-Chieh; Kuo, Kuang-Che; Chien, Chun-Chih; Hsiao, Chang-Chun; Chiu, Cheng-Hsun
Highlights: This culture-based study provided unbiased evidence on incidence rates, emerging serotypes and genotypes, and antimicrobial susceptibility of pneumococcal disease after implementation of pediatric PCV13 immunization in Taiwan. Pediatric national immunization of PCV13 has led to a reduction in the incidences of vaccine serotype pneumococcal disease including mucosal disease in children aged < 5 years and non-bacteremic pneumococcal pneumonia in adults. Emerging non-vaccine serotypes were identified mainly in non-invasive mucosal disease among children. Rapid capsular switch, clonal expansion, and declined penicillin and ceftriaxone susceptibility in NVTs are concerns in the current conjugate vaccine era. Summary: Objectives The multi-center clinical microbiological study in Taiwan aimed to evaluate the impact of childhood PCV13 immunization on pneumococcal disease, and the magnitude of serotype replacement in invasive and non-invasive pneumococcal disease among all age groups. Methods The study of culture-confirmed pneumococcal disease (CCPD) was conducted at four hospitals across Taiwan in 2015–2018. Pneumococcal pneumonia was defined as clinical diagnosis with positive sputum or bronchoalveolar lavage culture. Serotyping, multi-locus sequence typing, and antimicrobial susceptibility testing for penicillin and ceftriaxone were performed. Results A total of 1413 CCPD cases were identified. Invasive pneumococcal disease (IPD) accounted for 13.4% (190/1413) of CCPD. PCV7-type CCPD incidence declined among all age groups between 2015 and 2018. In adults aged 50–64 years, PCV7-type pneumococcal pneumonia incidence in 2018 was 72% lower than that in 2015, and all pneumococcal pneumonia incidence was 35% lower than that in 2015. In children, CCPD incidence was higher in 2018 than in 2015 (IRR 1.75 for age < 5 years, IRR 1.56 for age 5–17 years). Incidence of CCPD caused by non-PCV13-types, mainly 15A and 23A, increased significantly in those younger than 50 years. Serotypes 19A and 19F constituted the largest clonal complex, CC236/320 ( n  = 280, 19.8%). The rates of penicillin and ceftriaxone non-susceptibility were higher in PCV13-type isolates. Conclusions Childhood PCV13 immunization exerted an indirect protection to vaccine serotype clinically defined non-bacteremic pneumococcal pneumonia among adults, especially those between 50 and 64 years of age. Emerging non-PCV13 serotypes mainly caused non-invasive mucosal disease among children.